العقد الإلكتروني على ضوء القانون المدني الجزائري - - ملكي بركاهم - بلعباس يسرى (المسيلة, 2022)
لقد إنعكس التطور الحاصل في مجال المعلوماتية والإتصال، على جميع مجالات الحياة من بينها إب ا رم العقود مما ادى الى ظهور تقنية جديدة، إذ اصبحت تتم في بيئة إفت ا رضية تتجاوز الحدود الجغ ا رفية للدول ودون الحضور المادي للأط ا رف وذلك عن طريق استخدام مختلف الوسائل الإلكترونية وهذا ما يعرف بالعقد الإلكتروني، ولمواكبة هذا التطور وجب تنظيم علاقات بين الأف ا رد في هذا الشأن، فقد سارعت الدول الى تبني قوانين سواء على المستوى الدولي أو الداخلي لتنظيم هذه المسألة وعلى ق ا رر يأتي الدول أدخل المشرع الج ا زئري تعديلا على القانون المدني بموجب القانون 10 / 05 المؤرخ في 20 جوان 2005 وذلك بإضافة المادتين 323 مكرر 1 وتعديل المادة 327 ، إذا عرف الكتابة الإلكترونية في المادة 323 ، ونص على الإعتداء بالتوقيع الالكتروني في المادة 327 وأحال على المادة 323 مكرر 1 ، بخصوص الشروط الواجب توافرها فيه. وهذه الأحكام لا تعطي جميع الإشكالات التي تثيرها هذه العقود مما تعين على المشرع التدخل في هذه المسألة بصفة كلية. الكلThe development in the field of informatics and communication has been reflected in all areas of life, including contracting, which led to the emergence of a new technology for its convening, as it becomes a treasure in a virtual environment that transcends the geographical borders of countries and without the physical presence of the parties through the use of various electronic means. In order to keep pace with this development, it is necessary to regulate the relations between individuals in it. Countries have rushed to adopt laws, whether at the international or internal level, to regulate this issue. Like the rest of the countries, the Algerian legislator introduced an amendment to the civil law under Law 10/5 of June 20, 2005. By adding Articles 323 bis and 323 bis 1 and amending Article 327, as electronic writing was defined in Article 323 bis and stipulated that electronic signature should be considered in Article 327 and referred to Article 323 regarding the obligatory conditions. These provisions do not cover all the problems raised by contracts, which the legislator must intervene to regulate them completely. Key Words : Electronic contrcte, Algerian legeislator, The will, Electronic writing, Electronic signatureمات المفتاحية: العقد الإلكتروني، المشرع الج ا زئري، الإ ا ردة، الكتابة الإلكترونية، التوقيع
Keywords: االعقد الإلكتروني، المشرع الج ا زئري، الإ ا ردة، الكتابة الإلكترونية، التوقيع الالكتروني